DIDACTIC PRINCIPLES FOR FUTURE MUSIC TEACHERS IN CULTURAL AND EDUCATIONAL WORK IN EXTRACURRICULAR EDUCATION INSTITUTIONS - Sokolov Dmytro (International Journal of Innovative Technologies in Social Science, 2020)
In the article the author interprets didactic principles as a system of basic requirements, which should be followed in determining the content, forms of teaching, methods and means of teaching students, which will best contribute to the readiness of future music teachers for cultural and educational work in extracurricular education. The preparedness of future music teachers for cultural and educational work in out-of-school educational institutions is an integral personal education that determines the focus of students on parity interaction and the ability to successfully perform professional duties in the cultural and educational environment of out-of-school education. The following didactic principles are characterized: scientific, systematic and consistent, consciousness and activity of learning, accessibility, clarity, strength of knowledge, connection of theory and practice, emotionality, optimization of learning, control and correction of knowledge, the principle of education. The implementation mechanisms of these principles are revealed.